Sonocatalyzed hydrothermal preparation of lead titanate nanopowders - Rujiwatra A. (2014)
Nanoparticles of perovskite lead titanate, PbTiO3, were successfully prepared in a stoichiometric proportion at conspicuously low temperature and short reaction time of only 130 °C and 3.5 h. The employment of ultrasonic treatment prior to hydrothermal reaction, or so-called "sonocatalyzed hydrothermal reaction", was examined in detail. Roles of ultrasonic wave both as a catalyst to lower the hydrothermal reaction temperature affording the phase-pure PbTiO3 and as an external influence to provide better size homogeneity were discussed. © 2007 Elsevier B.V. All rights reserved.